Pengaruh Digital Marketing, Kualitas Pelayanan, dan Kualitas Produk terhadap Keputusan Pembelian di CV. Ifastore - Fadhli, Khotim; Ibrahim, Muhamad (REVITALISASI : Jurnal Ilmu Manajemen, 2024)
This paper investigates CV. ifastore consumer purchase decisions in relation to digital marketing, service quality, and product quality. The study approach is quantitative; data collected via a questionnaire comprising 89 respondents is followed by data analysis employing multiple linear regression with the SPSS program. With a t value of 7.551, which exceeds the t table value of 1.988 and a significance of 0.000, the study shows that digital marketing greatly influences buying decisions. Service quality also clearly influences the t value of 6.285 above the t table and the significance of 0.000. Product quality also significantly affects the t-value of 6.446 above the t-table, with a significance of 0.000. The computed F value 26.364 exceeds the F table. With a value of 0.000, it reveals that concurrently, digital marketing elements, service quality, and product quality significantly influence purchase decisions. This study concludes that customer purchase decisions are driven significantly by integrated marketing techniques. These results give CV. I fast strategic direction to enhance the quality of marketing strategies, products, and services to preserve competitiveness in the market.